Evaluation of Different Methods for Calculating the ROTI Index Over the Brazilian Sector. Issue 8 (27th July 2021) - Carmo, C. S.; Denardini, C. M.; Figueiredo, C. A. O. B.; Resende, L. C. A.; Picanço, G. A. S.; Barbosa Neto, P. F.; Nogueira, P. A. B.; Moro, J.; Chen, S. S.
Abstract: Ionospheric irregularities as plasma bubbles occur in the ionosphere, and generally, they are characterized by the low plasma density regions. The Rate Of TEC Index (ROTI) was defined in terms of the Total Electron Content (TEC) variation and is used to characterize these plasma bubbles. It is essential to evaluate the ROTI behavior since the ionospheric irregularities can cause fluctuations in the radio signal, interfering in the ionospheric data analysis. Therefore, we performed in this work a comparative study of five different methods available to calculate the ROTI to evaluate the most suitable over the Brazilian region. The ROTI was calculated over three GNSS stations at different latitudes: São Luís (SALU, 2°31′S, 44°16′W; dip: −3.8°), Cachoeira Paulista (CHPI, 22°40'S, 44°59'W; dip: −36.4°), and Santa Maria (SMAR, 29°41′S, 53°48′W, dip: −37°). The results show that the most viable method for calculating ROTI in the Brazilian region is based on the Slant TEC equation as defined by Cherniak et al. (2018), https://doi.org/10.1007/s10291‐018‐0730‐1 . Our results are supported by the comparison between the ROTI with TEC maps, ionograms collected at Fortaleza (FZA0M, 3°43'S, 38°32'W, dip: −15.8°), SALU, and CHPI and All‐Sky imagers collected at the São João do Cariri (SJCA, 7°23'S, 36°31'W, dip: −11°) and CHPI. Additionally, we observe Equatorial Plasma Bubbles (EPBs) in the Brazilian region using the ROTI index map. Key Points: We have compared five Rate Of TEC Index (ROTI) methods to evaluate the most suitable one for analyzing the equatorial ionospheric irregularities ROTI index maps are a very effective resource for observing and characterizing plasma bubbles in the Brazilian sector The irregularities observed in the ROTI index maps are more evident than in the total electron content maps